2019
DOI: 10.1136/bmjdrc-2018-000621
|View full text |Cite
|
Sign up to set email alerts
|

Association of socioeconomic status and DKA readmission in adults with type 1 diabetes: analysis of the US National Readmission Database

Abstract: ObjectiveTo identify patient and hospital predictors of recurrent diabetic ketoacidosis (DKA) admissions in adults in the USA with type 1 diabetes, focusing on socioeconomic indicators.Research design and methodsThis cross-sectional study used the National Readmission Database to identify adult patients with type 1 diabetes admitted for DKA between 2010 and 2015. The index DKA admission was defined as the first admission within the calendar year and the primary outcome was recurrent DKA admission(s) within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 27 publications
0
40
0
Order By: Relevance
“…In the present study, incidence and risk of hyperglycemic crises was disproportionately higher for patients with lower income, a finding supporting the need for policies and systems to ensure improved access to affordable glucose-lowering therapies. 25,26 Building on earlier work in different populations, 27,28 we found that for individuals with type 1 diabetes, the adjusted rate of hyperglycemic crises was 101.52 events per 1000 person-years among patients with low income (<$40 000) compared with 26.25 events per 1000 person-years among patients with high income (Ն$200 000). Income-based disparities in hyperglycemic crisis risk were also detected among patients with type 2 diabetes: 5.78 vs 2.23 per 1000 person-years, respectively.…”
Section: Discussionmentioning
confidence: 63%
“…In the present study, incidence and risk of hyperglycemic crises was disproportionately higher for patients with lower income, a finding supporting the need for policies and systems to ensure improved access to affordable glucose-lowering therapies. 25,26 Building on earlier work in different populations, 27,28 we found that for individuals with type 1 diabetes, the adjusted rate of hyperglycemic crises was 101.52 events per 1000 person-years among patients with low income (<$40 000) compared with 26.25 events per 1000 person-years among patients with high income (Ն$200 000). Income-based disparities in hyperglycemic crisis risk were also detected among patients with type 2 diabetes: 5.78 vs 2.23 per 1000 person-years, respectively.…”
Section: Discussionmentioning
confidence: 63%
“…About one in every five patients with DKA is readmitted within 30 days (33). In this study, we included only first admissions, as recurrent events would have significant impact on the interpretation of our results (lack of survival data outside the Emory Healthcare System).…”
Section: Discussionmentioning
confidence: 99%
“…We observed a high percentage of DKA and female/male ratio in our study. Interestingly, previous studies suggested that female sex was associated with an increased risk of DKA [ 36 39 ]. We suspect that this may be due to patient selection.…”
Section: Discussionmentioning
confidence: 99%